Handbook of Child and Adolescent Drug and Substance Abuse : Pharmacological, Developmental, and Clinical Considerations - Pagliaro, Louis A.; Pagliaro, Ann Marie (Hoboken : John Wiley & Sons, 2011)
An insightful and comprehensive guide covering the nature of drug and substance useand abuse by children and adolescentsThe Handbook of Child and Adolescent Drug and Substance Abuse provides a comprehensive, up-to-date review of the unique nature and extent of substance use by children and adolescents and its direct impact on their health, safety, and well-being, as well as that of their families and communities. Written from a developmental perspective, the chapters cover biological, psychological, and sociological theories for the abuse of alcohol and other substances by children and adolesc.
Front Matter -- Extent of Use and Pharmacological Considerations. The Psychodepressants -- The Psychostimulants -- The Psychodelics -- Developmental Considerations. Explaining Child and Adolescent Use of the Drugs and Substances of Abuse -- Exposure to the Drugs and Substances of Abuse from Conception Through Childhood -- Effects of the Drugs and Substances of Abuse on Learning and Memory During Childhood and Adolescence -- Clinical Considerations. Detecting Adolescent Use of the Drugs and Substances of Abuse: Selected Quick-Screen Psychometric Tests -- Dual Diagnosis Among Adolescents -- Preventing and Treating Child and Adolescent Use of the Drugs and Substances of Abuse -- Appendix: Abbreviations Used in the Text -- References -- Index -- About the Authors.
Print version record.
Keywords: Children -- Drug use -- Handbooks, manuals, etc; Teenagers -- Drug use -- Handbooks, manuals, etc; Adolescent psychiatry -- Handbooks, manuals, etc; Behavior therapy for children -- Handbooks, manuals, etc; Child psychiatry -- Handbooks, manuals, etc; Medicine; HEALTH & FITNESS -- Children's Health; MEDICAL -- Pediatrics; Children -- Drug use; Teenagers -- Drug use; Electronic books; Handbooks and manuals